Achieving the Optimal AgO Concentrations to Modulate the Anti-Trypanosoma cruzi Activity of Ag-ZnO/AgO Nanocomposites: In Vivo Investigations - José Rodrigues do Carmo Neto; Yarlla Loyane Lira Braga; Pablo Igor Ribeiro Franco; Jordana Fernandes de Oliveira; Rafael Obata Trevisan; Karen Martins Mendes; Milton Adriano Pelli de Oliveira; Mara Rúbia Nunes Celes; Anielle Christine Almeida Silva; Juliana Reis Machado; Marcos Vinícius da Silva (MDPI AG, 2024)
Background/Objectives: For the development of new treatments, the acute phase of Chagas disease (CD) in experimental models acts as a filter to screen out potentially effective interventions. Therefore, the aim of this study was to evaluate ZnO nanocrystals and Ag-ZnO/AgO nanocomposites containing different proportions of silver (ZnO:5Ag, ZnO:9Ag and ZnO:11Ag) in an experimental model of the acute phase of CD. Methods: C57Bl/6 mice were infected with 1000 forms of the Colombian strain of T. cruzi. The treatment was carried out by gavage with 5 mg/kg/d for 7 consecutive days from the first detection of parasitemia. Weight, parasitemia and survival were assessed during treatment and up to the day of euthanasia. After euthanasia, the cardiac and intestinal parasitism, inflammatory infiltrate, collagen deposition and cytokine dosages were analyzed. Results: It was observed that the nanocomposites ZnO:9Ag and ZnO:11Ag were the most effective in reducing parasitemia and increasing the survival of the infected animals. However, pure ZnO induced the maintenance of parasitemia and reduced their survival. The ZnO:9Ag and ZnO:11Ag nanocomposites were able to reduce the number of cardiac amastigote nests. In addition, they were responsible for reducing TNF-α and IL-6 in situ. ZnO:9Ag and ZnO:11Ag induced a reduction in the intestinal inflammatory infiltrate and neuronal protection in the myenteric plexus, as well as reducing TNF-α in situ. Conclusions: Based on these results, it is suggested that there is an ideal concentration in terms of the proportion of Ag/AgO and ZnO in nanocomposites for use against CD. Thus, ZnO:9Ag or ZnO:11Ag nanomaterials are potential candidates for the development of new biotechnological products for the therapy of CD.